Scalable Li1.5Al0.5Ge1.5(PO4)3 thin membrane prepared by tape-casting for large-scale lithium–air battery application. (23rd August 2020) - Zhu, Yaqi; Chen, Gongxuan; Sun, Jianguo; Wang, Jiakai; Wu, Tian; Dai, Wei; Lu, Li
ABSTRACT: Thin NASICON-type Li1.5 Al0.5 Ge1.5 (PO4 )3 solid electrolyte membrane is successfully fabricated through tape-casting. A high density of 3.28 g cm −3 of the membrane with a porosity of 4.5% has been achieved when it is sintered at 900°C for 11 h. The membrane shows a comparative ionic conductivity with that of the glass-ceramic pellets. The total ionic conductivity of the present membrane is 2.62 × 10 –4 S cm −1 at room temperature, and it maintains a stable conductivity of 1.3 × 10 –4 S cm −1 in a 0.5 M LiOH and 0.5 M Li3 PO4 buffer solution, which can fully afford the requirements of the membrane used in lithium–air batteries. Graphical Abstract: High-density thin LAGP membrane with comparative ionic conductivity has been successfully prepared by tape-casting, which can fully afford the essential requirements of using in Li–air battery.